2020
DOI: 10.1039/d0tc03660a
|View full text |Cite
|
Sign up to set email alerts
|

Reducing lifetime in Cu(i) complexes with thermally activated delayed fluorescence and phosphorescence promoted by chalcogenolate–diimine ligands

Abstract: Luminescent copper(I) complexes have drawn attention due to their promising performance as alternative optoelectronic materials to the well-known heavy transition metals complexes. Herein, we report the synthesis of six luminescent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…The HOMO orbital centered at copper-aminophosphine moiety maximize the HOMO and LUMO overlap for C2, while it is minimized for C3 by decreasing or increasing the spatial separation of these orbitals, respectively (Figure S9). The HOMO and LUMO overlap directly impacts the ΔE(S 1 À T 1 ) , [24] as observed from the spectroscopic studies, and agrees well with the calculated ΔE(S 1 À T 1 ) using the vertical energy difference for such states (Table 4). The computed energy separation shows higher values than the experimental ones due to a known issue in DFT for such charge transfer states.…”
Section: Theoretical Modeling Of the Electronic Structure And Photophysical Interpretationssupporting
confidence: 86%
See 1 more Smart Citation
“…The HOMO orbital centered at copper-aminophosphine moiety maximize the HOMO and LUMO overlap for C2, while it is minimized for C3 by decreasing or increasing the spatial separation of these orbitals, respectively (Figure S9). The HOMO and LUMO overlap directly impacts the ΔE(S 1 À T 1 ) , [24] as observed from the spectroscopic studies, and agrees well with the calculated ΔE(S 1 À T 1 ) using the vertical energy difference for such states (Table 4). The computed energy separation shows higher values than the experimental ones due to a known issue in DFT for such charge transfer states.…”
Section: Theoretical Modeling Of the Electronic Structure And Photophysical Interpretationssupporting
confidence: 86%
“…At low energy, close to 400 nm a broad absorption band is observed, which is attributed to a metal-to-ligand charge-transfer (MLCT) transition as suggested by DFT calculations (see section 2.4). [6,7,9,12,24] The absorption spectra of the complexes dispersed in PMMA were found to be very similar to the solution (Figure S6). By exciting the complexes dispersed in PMMA at the lower energy band, a broad and unstructured line shape emission spectra was observed (Figure 2), which agrees with the MLCT nature of the emitting state (see section 2.4).…”
Section: Photophysical Properties and Detailed Tadf Mechanismmentioning
confidence: 79%
“…Their synthesis, purification, structural characterization and photophysical behavior supported by theoretical studies were previously reported. [18] The previous photophysical studies using steady-state and time-resolved spectroscopy showed emission decay of these complexes mainly by the TADF mechanism, combined with an additional phosphorescence. A reduced photoluminescence lifetime of about 1 μs due to the S and Se containing ligands in S1, Se1, S2 and Se2 was observed compared to their reference compounds C1 and C2 was observed (> 2 μs) ( Table 1).…”
Section: Molecular Structure and Characterizationmentioning
confidence: 89%
“…The device without EIL/ETL exhibited only one peak at 578 nm, redshifted in comparison to the photoluminescence spectrum of C2, due to dependence on the medium of the MLCT emission. [18] The device with EIL/ETL also exhibited a shoulder around 435 nm coming from the PFNBr emission due to hole accumulation at the EML/ETL interface as consequence of the electron injection mechanism. [23] The low PFNBr HOMO level (5.6 eV), which does not block the holes, allows charge recombination in the ETL.…”
Section: Electroluminescence Propertiesmentioning
confidence: 95%
See 1 more Smart Citation